Congruent spatial acid temporal foraging by a dominant ant (Hym, Formicidae) and its replacement in an assemblage in a large urban structure in southeastern Brazil - Fowler, H. G.; Bueno, O. C. (Wiley-Blackwell, 1996)
At fixed bait stations in a large institutional setting in Brazil, the temporal and spatial pattern of usage of the dominant species of ant was studied. The ant Crematogaster cf. magnifica, was found in 91% of sampling points. These studies were conducted using the same points as a previous study of the then dominant ant, Monomorium phauaonis, which was found to have declined from 93% to 3% spatial point occupation. The frequency of point usage during this study was significantly different from the Poisson distribution for both species, indicating non-random use of space. Crematogaster cf. magnifica was significantly more spatially exclusive than had been documented for M. pharaonis, and the probability of points originally occupied by M. phauaonis later becoming occupied by C. cf. magnifica was in excess of 90%. Temporal bait exploitation patterns of the two species did not differ. These data demonstrate that structural ant communities can change over time without human intervention, although short-term stability is characteristic of the urban dominant ants in subtropical Brazil.